Serving up love ebook A four-in-one harvey house brides collection. - Peterson, Tracie (2019)
This intriguing novella collection crosses the country—from Kansas to Texas, the Grand Canyon to New Mexico—with tales of sweet romance while exploring the fascinating history of the Harvey Girls: young women seeking adventure and independence who worked in hotels throughout the country from the early 1880s to the late 1920s.